Mental Health as a Determinant Factor in Academic Performance: A cross-sectional study among medical students of Mashhad University of Medical Sciences, Mashhad, Iran - Shabnam Niroumand; Moustafa Naseroddin; Mahdi Talebi; Maliheh Dadgarmoghaddam; AmirAli Moodi Ghalibaf (Mashhad University of Medical Sciences, 2021)
Background: Students' mental health has a strong relation to their quality of life and their academic success. This study aims to assess the mental health of medical students throughout different educational courses including pre-clinical, externship, and internship, and its association with students' academic performance at Mashhad University of Medical Sciences.Methods: This cross-sectional analytical study was performed on all medical students studying in the first semester of pre-clinical course, at the beginning of the externship, and the beginning of the internship at Mashhad University of Medical Sciences in 2019. In this study, a general mental health questionnaire containing 12 questions (GHQ-12) was used. Data analysis was performed using chi-square and t-test using SPSS 16.Results: The mean age of students was 22.61 + 1.79. In this study, approximately 40% of students scored higher than the threshold for the GHQ-12 questionnaire, indicating that they experienced more psychological distress than others. The highest score was related to the and the lowest score was related to externs. In addition, although students with higher academic scores have lower psychological stress and better mental health status than other students, these differences were not significant.Conclusion: The results showed that overall nearly half of medical students based on the GHQ-12 questionnaire are subject to psychological stress. These stresses not only affect their mental health but also affect their academic performance.